FACTORS OF ADAPTATION OF FOREIGN HIGHER EDUCATION ACQUIRES - Borysiuk, Iryna; Fizor, Natalia; Zamkovaja, Alyona; Molodan, Yuliia; Valivodz, Iryna; Аkisheva, Alina (Sworld-Us Conference proceedings, 2023)
The work examines the main factors affecting the adaptation of foreign students, the problems of students' adaptation to life and study in Ukraine, especially to the language barrier, especially difficulties related to the Ukrainian language, insufficient